Le niveau de scolarisation au primaire : entre mesures, usages et enjeux - Étienne Gérard; Marc Pilon (Les éditions de la Maison des sciences de l'Homme, 2005)
In the countries of the so-called "South", in this case African countries, the percentage of children in school is one of the main indicators used to evaluate school systems and the delivery of "education for all" (EPT). Because it refers to different populations (children of school age and children at school) measured by different institutions, this ratio raises interpretation and analysis problems. This article examines first some of them. Then, it discusses what is at stake in the construction and use of this indicator, and finally what is not measured but should be, if the analysis of the level of schooling was to be considered not only from the supply side, but extended to the social factors of the demand.